2014
DOI: 10.1021/jm401906v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Antimetastatic Agents Predicated upon Dihydromotuporamine C and Its Carbocyclic Derivatives

Abstract: The motuporamines isolated from the sea sponge Xestospongia exigua are of biological interest because of their unique antimigration and antiangiogenic properties. Key bioactive features were found to be a saturated 15-membered heterocycle and a norspermidine motif. This paper describes new analogues that modulate the cytotoxicity of this compound class and have enhanced antimigration properties. By movement of the polyamine chain outside the ring, new carbocycles were discovered that doubled the antimigration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 40 publications
1
56
0
Order By: Relevance
“…Moreover, in the structure of CHENSpm and CPENSpm, the alkylation of the distant nitrogen in the polyamine chain plays an important role in increasing the activity in cancer cells and decreasing the toxicity in normal cells. Our group and others find that natural products with homospermidine moiety without the alkylation of the distant nitrogen in the polyamine chain showed good activities (Casero and Marton, 2007;Wang et al, 2012;Muth et al, 2013Muth et al, , 2014Li et al, 2016Li et al, , 2018Dai et al, 2017a;Ma et al, 2017aMa et al, ,b, 2018Skruber et al, 2017;Casero et al, 2018;Phanstiel, 2018;Liu et al, 2019). However, naphthalimide conjugates with the alkylation of the distant nitrogen in the polyamine chain are rarely reported.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, in the structure of CHENSpm and CPENSpm, the alkylation of the distant nitrogen in the polyamine chain plays an important role in increasing the activity in cancer cells and decreasing the toxicity in normal cells. Our group and others find that natural products with homospermidine moiety without the alkylation of the distant nitrogen in the polyamine chain showed good activities (Casero and Marton, 2007;Wang et al, 2012;Muth et al, 2013Muth et al, , 2014Li et al, 2016Li et al, , 2018Dai et al, 2017a;Ma et al, 2017aMa et al, ,b, 2018Skruber et al, 2017;Casero et al, 2018;Phanstiel, 2018;Liu et al, 2019). However, naphthalimide conjugates with the alkylation of the distant nitrogen in the polyamine chain are rarely reported.…”
Section: Introductionmentioning
confidence: 92%
“…Resurgence in the interest of natural polyamines as an anticancer strategy results from advances in our understanding of polyamine metabolism and their alterations in cancer (Casero and Marton, 2007;Casero et al, 2018;Phanstiel, 2018). Natural products with polyamine moiety have been found to be a promising strategy to enhance targeting properties and deduce the toxicities (Muth et al, 2013(Muth et al, , 2014Skruber et al, 2017). Polyamine analogs CHENSpm and CPENSpm in Figure 1 have entered in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…F14512, an epipodophyllotoxin-spermine conjugate, is perhaps the most promising compound which is presently being evaluated in phase I trials [16,17,18,19]. Our work demonstrated that derivatives incorporating an aromatic imide skeleton or connecting to a polyamine linker such as spermidine or homospermidine, exhibit marked cell selectivity and lung cancer metastasis inhibition [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. These findings stimulated us to search for more promising imide scaffolds suitable for polyamine modification.…”
Section: Introductionmentioning
confidence: 96%
“…Currently, extensive researches have emphasized the fact that polyamine conjugates acting as promising antitumor candidates are becoming increasingly important in the polyamine field [11,12,13,14,15]. F14512, an epipodophyllotoxin-spermine conjugate, is perhaps the most promising compound which is presently being evaluated in phase I trials [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The motuporamines (originally isolated from the marine sponge Xestospongia exigua ) were selected because their amphiphilic architectures comprise a large hydrophobic macrocycle with an appended polyamine motif ( 1 – 3 , Scheme ). A series of motuporamine derivatives ( 4 – 6 ) was prepared along with a series of related anthracenyl‐polyamine derivatives ( 7 a – d ). These amphiphilic polyamines have large hydrophobic substituents to facilitate interaction with the bacterial membrane.…”
Section: Introductionmentioning
confidence: 99%